'Dances with Daffodils': Life as a Flower-picker in Southwest England. (April 2022) - Manolchev, Constantine; Ivan,
Physically demanding and low-paid, work in the agri-food sector has been described in the literature as equal measures precarious and exploitative. In order to investigate the everyday realities of a flower-picker's job, we trace Ivan's journey from a Bulgarian university to the daffodil fields of Cornwall, UK. Following two rounds of successful promotions, Ivan's work is no longer governed by the seasonal rhythms of the flower-picking industry. However, as a welfare manager, he now faces hidden and open resistance from other migrant pickers whose work he oversees. Speaking to us at the height of the picking season and having worked seven days a week for months, Ivan is struggling. He has no time to complete his application to remain in the UK and is becoming mindful of the gap between the expectations placed on him by his employer, and the recompense offered in return.